PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS POTENSI LOKAL UNTUK PEMBELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DI SMA - Triana Rejekiningsih; Mochamad Kamil Budiarto; Sudiyanto Sudiyanto (Balai Besar Guru Penggerak Jawa Timur, 2021)
This study aims to develop interactive multimedia products based on local potential that are suitable for use in handcrafted learning and entrepreneurship in high schools. This research is a research and development (Research and Development) with a 4-D model (Define, Design, Develop, Disseminate) which takes place in Susukan 1 State Senior High School, Cirebon. The subjects of this study were 29 students, two educators and two media and material expert. The research instrument used a needs analysis questionnaire and observation sheet at the definition stage, then a questionnaire for validation of media experts, material experts, educators and students for the development stage. The result of this research and development is an interactive multimedia product that is suitable for learning craftsmanship and entrepreneurship. The research results show that students have a positive view of interactive multimedia development, besides that the results of developing interactive multimedia products based on local potential have gone through the validation and assessment stages of all media experts with a score of 4.6 (very good), material experts 4.8 ( very good), educators 4.3 (good), and students 4.2 (good), so that overall interactive multimedia products have met learning needs and are included in the appropriate category for use in the learning process of handcraft and entrepreneurship in high school.AbstrakPenelitian ini memiliki tujuan untuk mengmbangkan produk multimedia interaktif berbasis potensi lokal yang layak digunakan pada pembelajaran prakarya dan kewirausahaan di Sekolah Menengah Atas. Penelitian ini adalah penelitian dan pengembangan (Research and Development) dengan model 4-D (Define, Design, Develop, Disseminate) yang mengambil lokasi di Sekolah Menengah Atas Negeri 1 Susukan, Kabupaten Cirebon. Subjek penelitian ini adalah 29 peserta didik, dua pendidik serta dua validator ahli media dan materi. Instrumen penelitian menggunakan angket analisis kebutuhan dan lembar observasi pada tahap pendefinisian, kemudian angket untuk validasi ahli media, ahli materi, pendidik serta peserta didik untuk tahap pengembangan. Hasil dari penelitian dan pengembangan ini adalah produk multimedia interaktif yang layak digunakan untuk pembelajaran prakarya dan kewirausahaan. Melalui hasil penelitian menunjukkan siswa memiliki pandangan yang positif terhadap pengembangan multimedia interaktif, disamping itu hasil pengembangan produk multimedia interaktif berbasis potensi lokal telah melalui tahapan validasi serta penilaian dari seluruh ahli media dengan skor 4,6 (sangat baik) , ahli materi 4,8 (sangat baik), pendidik 4,3 (baik), dan siswa 4,2 (baik), sehingga secara keseluruhan produk multimedia interaktif telah memenuhi kebutuhan pembelajaran serta termasuk dalam kategori layak untuk digunakan dalam proses pembelajaran prakarya dan kewirausahaan di SMA.